Bencana Nasional Covid-19: Adakah Reaksi Pasar Modal Indonesia? - Iwan Kusmayadi; G.A Oktaryani; Muhamad Ahyar; Laila Wardani; Djoko Suprayetno (Postgraduate, University of Mataram, 2023)
This study aims to examine the information content of the Covid-19 national disaster emergency announcement on the reaction of the Indonesian capital market. The population of this study is all public companies that list their shares on the Indonesia Stock Exchange (IDX). By using purposive sampling, a sample of 659 companies was selected. Using historical data, namely the closing price (close) of individual shares and the composite stock price index, IHSG (composite stock price index). The observation period is 71 days, each consisting of an estimation period (60 days) and a window period. using 11 days. This research shows evidence that the capital market in Indonesia has reflected inefficient conditions, especially in the 4 days around the announcement of the Covid-19 national disaster emergency in Indonesia. While the other 7 (seven) days cannot provide opportunities for investors, especially to get significant abnormal returns. These results also show evidence that the capital market in Indonesia is efficient. Future researchers can complement it by using different models or comparing between models in measuring abnormal returns. Subsequent research can also classify the impact of the Covid-19 event by comparing between sectors in the 9 sectors on the IDX. In addition, there are opportunities for future research to conduct studies of different events.